ANALISIS PEMEROLEHAN BAHASA PADA ANAK USIA 5 TAHUN DI DESA OELNASI KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Maya Imelda Samene; Labu Djuli; Narantoputrayadi Makan Malay (Jurnal Lazuardi, 2026)
This study aims to describe language acquisition in five-year-old children in Oelnasi Village, Kupang Tengah District, Kupang Regency, which includes the acquisition of Dawan Language, Indonesian Language, and Kupang Malay Language. This research employs a descriptive qualitative method with a psycholinguistic approach, particularly the behavioristic theory. Data were collected through observation, interviews, and documentation involving children and their parents. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that five-year-old children in Oelnasi Village have acquired the three languages at different levels. Dawan Language acquisition occurs through family interaction and social environment, Indonesian Language is acquired through formal contexts and education, while Kupang Malay Language is acquired through daily social interactions. Language acquisition in children is influenced by environmental factors, stimuli, and reinforcement from parents and the surrounding community. This study shows that a multilingual environment plays an important role in early childhood language acquisition.